The Market for Funeral Services: Transformation of Ritual Rules into Market Rules - МоисееваЕкатерина Николаевна (Journal of Economic Sociology, 2010)
The market for funeral services is one dealing with the most sacred and emotionalised objects. Similarly to the life insurance industry and the organ transplant industry it is conditioned by the fact of death. The paper considers the following issues: what is sold out and purchased on this market? What are the qualities of the goods offered? On which terms are economic transactions arranged? And which factors define buyers’ rational behaviour? A major insight of the study is that a cultural construct of deserving funerals is traded here. Market for funeral services can be viewed as an interplay between sacred and secular. Understanding of cultural restraints governing market transactions allows us to reveal how ritual rules are transformed into market rules.